Discourse on the Political Role of Civil Society in Building Democracy in Indonesia from the Perspective of Intellectuals in East Java - Wing Artha, Gratia (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
Post-reform, Indonesian civil society faces significant challenges in building democracy. This study examines the discourse on the political role of civil society according to intellectual groups in Surabaya and Malang, East Java. This research investigates intellectual groups in both cities that have established higher education bases and capabilities to enliven the provincial political space, using qualitative methods. Data were collected through in-depth interviews, observations, and documentation of informants' thoughts from journals, books, and media articles. The main findings identify three intellectual groups with different discourses: 1) Critical Group, where civil society plays a role in building democracy by becoming a controlling force against state power; 2) Moderate Group, where civil society needs to cooperate with the state in building democracy; 3) Hybrid Group, where civil society needs to cooperate with the state while maintaining a critical stance. This research reveals the complexity of East Java intellectuals' views on the political role of civil society post-reform. The three groups demonstrate a spectrum of thought from oppositional control to critical collaboration, reflecting the dynamics of state-civil society relations in Indonesia's democratization process.